Partial plantar fasciectomy for the treatment of plantar fibromatosis - Costa, Lucas Plens de Britto; Fonseca, Lucas Furtado da; Lemos, André Vitor Kerber Cavalcanti; Pereira, Vinicius Felipe; César Netto, César de; Raduan, Fernando Cepollina; Nery, Caio Augusto de Souza; Mansur, Nacime Salomão Barbachan (Journal of the Foot & Ankle, 2021)
Objective: We describe a series of patients treated with resection of the affected band. We assessed functional outcome, recurrence rate, and surgical wound complications, comparing these data with the available literature. Methods: This retrospective study (level of evidence IV) included 14 patients (17 feet) diagnosed with plantar fibromatosis in the medial portion of the fascia that was refractory to conservative treatment. All operations were performed between December 2016 and November 2018. All patients were assessed for symptom improvement and major and minor complications, in addition to recurrence during the study period. Results: Our sample included 9 men and 5 women, whose mean age was 40.6 years (15-63). All of the patients underwent partial fasciectomy of the medial fascial band with margins of at least 2 cm. There was recurrence in 5 of the 17 feet (29%), but only two required further intervention. Wound dehiscence occurred in 3 patients (17%), and one of the cases was severe, requiring plastic surgery. Two feet showed signs of injury to the digital branch of the medial plantar nerve. Conclusion: Partial plantar fasciectomy is an alternative treatment for plantar fibromatosis (Ledderhose’s disease). Our results agree with the literature in terms of recurrence and postoperative complications. The moderate rate of complications must be taken into account when indicating this procedure. Level of Evidence IV; Therapeutic Studies; Case Series.